1981
DOI: 10.1042/cs0600617
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Amounts of the Collagen Chains α1(I), α2 and α1(III) in the Skin of 31 Patients with Osteogenesis Imperfecta

Abstract: 1. The relative amounts of type III and type I collagen, determined as the ratio of their constituent alpha 1(III) and alpha 1(I) chains, have been measured by interrupted electrophoresis of pepsin extracts of skin collagen from 31 patients with osteogenesis imperfecta of varying severity, and from six clinically unaffected family members. In 18 patients the ratio of the alpha 1(I) to alpha 2 chains of type I collagen has also been measured. 2. In the 15 patients with osteogenesis imperfecta classified as mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…It is likely that this clinical heterogeneity reflects differences in the fundamental molecular abnormalities. At present, there is growing evidence that some of these disorders result from defects in the synthesis or maturation of collagen [11,12]. All but one of the high values for a2HS-glycoprotein in plasma were found in patients with Sillence's type I OI; in part, this may reflect the total number of patients with this type.…”
Section: Discussionmentioning
confidence: 93%
“…It is likely that this clinical heterogeneity reflects differences in the fundamental molecular abnormalities. At present, there is growing evidence that some of these disorders result from defects in the synthesis or maturation of collagen [11,12]. All but one of the high values for a2HS-glycoprotein in plasma were found in patients with Sillence's type I OI; in part, this may reflect the total number of patients with this type.…”
Section: Discussionmentioning
confidence: 93%
“…In a comment, Spranger pointed out that there is a report on an a girl who has now to be classified as OI type III, while her newborn brother has to be diagnosed as subtype IIB [6]. These findings were later confirmed in intact bone [5,10,23] and now appear characteristics of this OI type. As early as 1920, Bauer suggested that OI was a systemic disease of the connective tissue due to a disordered synthesis of collagen [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The collagen concentration was measured as previously described. 12 Type I and type III injectable human collagen passed the required bacteriology, virology, and pathology tests. Type I and type III injectable human collagen is packaged in 2-mL syringes in a physiological saline buffer solution containing 0.3% lidocaine at a pH of 7.2.…”
Section: Type I and Type Iii Injectable Human Collagenmentioning
confidence: 99%